2020
DOI: 10.1136/jitc-2019-000467
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury associated with immune checkpoint inhibitor therapy: incidence, risk factors and outcomes

Abstract: BackgroundImmune checkpoint inhibitors (ICPi) are a novel and promising anti-cancer therapy. There are limited data on the incidence, risk factors and outcomes of acute kidney injury (AKI) in patients receiving ICPi.MethodsWe conducted a cohort study of patients receiving ICPi at our center between 2010 and 2017 via electronic health record. The primary outcome was AKI (increase of >50% from baseline serum creatinine (sCr)). Risk factors for AKI were assessed using logistic regression. Survival among those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
157
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(177 citation statements)
references
References 31 publications
13
157
6
1
Order By: Relevance
“… 5 Kidney toxicity while on ICI therapy occurs in up to 17% in reported series, but only a fraction is related to ICI, varying from 1% to 5% (depending on the type of ICI or use of combined ICI agents). 10 , 11 , 12 , 13 , 14 , 15 Acute interstitial nephritis (AIN) is the most common histopathological lesion, and depending on the severity of the renal or extra-renal iRAE, further treatment with immunotherapy may be limited. 16 In general, the use of systemic cancer agents is associated with AKI of diverse etiologies, and it is important to understand the likely cause so as to not unnecessarily limit future chemotherapeutic treatment options.…”
mentioning
confidence: 99%
“… 5 Kidney toxicity while on ICI therapy occurs in up to 17% in reported series, but only a fraction is related to ICI, varying from 1% to 5% (depending on the type of ICI or use of combined ICI agents). 10 , 11 , 12 , 13 , 14 , 15 Acute interstitial nephritis (AIN) is the most common histopathological lesion, and depending on the severity of the renal or extra-renal iRAE, further treatment with immunotherapy may be limited. 16 In general, the use of systemic cancer agents is associated with AKI of diverse etiologies, and it is important to understand the likely cause so as to not unnecessarily limit future chemotherapeutic treatment options.…”
mentioning
confidence: 99%
“…Immune-related toxicities involving the kidneys, the most described being acute interstitial nephritis, occurs in about 2%-4% of patients. [48][49][50][51] ICI have also been associated with electrolytes disturbances, the most frequent being hyponatremia. 52 A meta-analysis of 48 clinical trials of PD-1 inhibitor therapy in different cancer types showed an overall hyponatremia incidence of 1.2% and hyponatremia accounted for more than 53% of Grade 3-5 reported electrolytes abnormalities.…”
Section: Immune Checkpoint Inhibitorsinduced Hyponatremiamentioning
confidence: 99%
“…However, CTLA-4 Ig does not significantly affect human Th1 cells in renal graft tissue [ 74 ]. Moreover, immunotherapy with CTLA-4 antibodies causes AKI in some cancer patients [ 75 , 76 ].…”
Section: The Differences In Adaptive Immunity Among Rodents Large Anmentioning
confidence: 99%